Flipped Learning and Smart Phone; Their Impact on Students’ Achievement and Performance - Abuhmaid, Yaser; Abu-Khalifeh, Ibtisam (DIRASAT: EDUCATIONAL SCIENCES, 2017)
The study, on one hand, is an action research aims to figure Out the impact of corporate implication of Flipped and mobile learning supported by Smart Phones on students’ performance in the three lower cognitive achievement levels in Bloom’s Taxonomy including Remembering, Understanding, and Applying targeting undergraduate classroom teachers at FESA in Jordan. On the other hand, perceptions regard learning and teaching experience of the experimental group is reviewed. The study tends also to raise undergraduate classroom teachers awareness about using mobile technology in ways activate learning and makes mobile technology an efficient element in the learning process through engaging students authentically in such a learning experience.